Enhancement of mechanical and flame-retardant properties of Acacia hybrid through the treatment of a combination of styrene-acrylic copolymer and sodium silicate - Thi Tham, Nguyen; Cong Chi, Tran; Duy Hung, Phan; Hien Mai, Trinh; Trong Kien, Nguyen; Thi Anh Hong, Pham (Journal of Forestry Science and Technology, 2024)
The mechanical and flame-retardant properties of Acacia hybrid wood were studied through the treatment of an aqueous solution containing a styrene-acrylic copolymer (SC) and sodium silicate (SS). The results showed a significant increase in the mechanical properties of SC/SS-treated wood. Specifically, the modulus of rupture (MOR) and modulus of elasticity (MOE) improved by up to 71.54% and 53.65%, respectively. The surface hardness of the cross-section and radial section also increased by 37.24% and 46.65%, respectively. The treated wood’s weight percentage gain (WPG) reached up to 23.31%. The largest leaching rate (LR) of treated wood was only 8.01%, suggesting this treatment has obvious effects in fixing the SS in the wood. However, it did not cause positive bulking efficiency (BE) and anti-swelling efficiency (ASE). The incorporation of SS with SC resulted in the decomposition of polysaccharides at a lower temperature while increasing the limiting oxygen index (LOI), which was 34.95% higher than that of untreated wood, making it more difficult to ignite. Scanning electron microscopy (SEM) results showed that the SC/SS deposited in the cell lumina after polymerization, but significant structural changes occurred, including vessel and cell wall deformation due to the partial dissolution of hemicellulose and lignin from the cell wall in the alkaline solution. The results of this study demonstrate the feasibility of applying the SC/SS combination treatment to wood in practical applications.